The opioid epidemic and US culture : expression, art, and politics in an age of addiction - Stimeling, Travis D. (West Virginia University Press, 2020)
"The Opioid Epidemic and US Culture brings a new set of perspectives to one of the most pressing contemporary topics in Appalachia and the nation as a whole. A project aimed both at challenging dehumanizing attitudes toward those caught in the opioid epidemic and at protesting the structural forces that have enabled it, this edited volume assembles a multidisciplinary community of scholars and practitioners to consider the ways that people have mobilized their creativity in response to the crisis. Written for an audience of people working on the front lines of the opioid crisis, the book is essential reading for social workers, addiction counselors, halfway house managers, and people with opioid use disorder. It will also appeal to the community of scholars interested in understanding how aesthetics shape our engagement with critical social issues, particularly in the fields of literary and film criticism, museum studies, and ethnomusicology"--